Facilitators and Barriers of Heart Surgery Discharge: Patients' and Nurses' Narrative Accounts. Issue 4 (July 2016) - Lapum, Jennifer L.; Fredericks, Suzanne; Liu, Linda; Yau, Terrence M.; Retta, Bruktawit; Jones, Vaska M.; Hume, Sarah
Abstract : Background: Optimal patient recovery from open-heart surgery relies on effective discharge planning and education. However, the nature of the discharge experience has not been clearly described. Objective: The study purpose is to explore patients' and nurses' narrative accounts of the facilitators and barriers of heart surgery discharge. Methods: A qualitative study was employed using a narrative methodology that elicited and analyzed stories. This research was conducted in a large, urban hospital in Ontario, Canada. A total of 17 patients and nurses were recruited. Five female and 5 male patients were recruited from a preoperative clinic. Ages ranged from 37 to 80 years. Seven nurses were recruited from inpatient cardiovascular units. They had 2 to 19 years of cardiovascular nursing experience. Semistructured, narrative-based interviews were conducted. Two interviews were conducted with each patient at 1 week after discharge and at 4 to 6 weeks. One interview was conducted with each nurse. Results: Findings indicate that although the preoperative period was identified as an effective time for discharge preparation, the patient's cognitive capacity was limited during the postoperative phase of surgery. Both nurses and patients also found that insufficient time impeded the discharge process and limited individualized discussions. The structured and standardized delivery of discharge information affected patients' capacity to apply it to the particularities in their own lives and homes. The fostering of therapeutic relationships created a space where patients felt comfortable sharing their concerns and nurses learned more about patients and thus could better tailor the discharge approach. Conclusions: Study recommendations include group and scenario-based education in which patients and nurses brainstorm about how to apply the discharge information to the particularities of patients' lives and homes. Provision of support needs to be bolstered during the home period, where patients have timely opportunities to discuss their concerns and questions with practitioners or possibly peers.